Effect of Testing Configuration in Semi-Circular Bending Fracture of Asphalt Mixtures: Experiments and Statistical Analyses. Issue 5 (May 2019) - Nsengiyumva, Gabriel; Kim, Yong-Rak
The semi-circular bending (SCB) test is a simple, efficient, and easily applicable method in the pavement community to characterize fracture behavior. This makes it widely used as a quality control (QC) and quality assurance (QA) approach at several transportation agencies. However, public–private testing laboratories have implemented SCB test methods using different load-support fixture conditions with an insufficient understanding of how the conditions affect the results and testing variability. This could be particularly problematic when using SCB test results obtained from different load-support fixtures as QC–QA (or pass/fail) purposes. This study investigated the effect of SCB testing configurations on test results and their variability by conducting tests using six different load-support fixtures. Several fracture-related indicators such as fracture energy, flexibility index, peak load, and the coefficient of the cracking index resulting from the six different load-support fixtures were compared. Test results and statistical analyses showed that SCB tests generally showed repeatable results, whereas load-support fixtures can affect test results and their repeatability, thus care should be taken when choosing a testing fixture. The addition of roller springs generally increased the variability of the test results. It appears that the mid-span jig was detrimental to testing repeatability, and friction at the support should be avoided because it can erroneously increase fracture resistance with a higher variability.